Risiko Harga Daging Ayam Ras di Tingkat Produsen dan Konsumen di Sulawesi Selatan - Albab, Ulil; Mardiyati, Sri; Nurdin, Nurdin; Tahir, Ratnawati; Amruddin, Amruddin; Jamili, Muhammad Arsan (Jurnal Ilmu dan Industri Peternakan, 2025)
Broiler chicken is consumed widely across Indonesia, particularly in South Sulawesi, where demand for broiler chicken continues to increase annually. South Sulawesi is a relatively large region with a substantial population, particularly in urban areas. This study aims to analyze broiler chicken price risk at the producer and consumer levels in South Sulawesi and identify factors influencing price volatility. Broiler chicken price volatility directly impacts the welfare of farmers and consumer purchasing power, particularly amidst seasonal demand dynamics and fluctuating feed costs. Secondary data was obtained from the Strategic Food Price Information Center (PIHPS) for the period January-December 2025. The method used to measure broiler chicken price risk is the coefficient of variation (CV). The results indicate that broiler chicken price risk is not entirely borne by producers, but rather by wholesalers. This finding aligns with agribusiness marketing theory, which states that market players in the middle of the marketing chain tend to bear greater risks.